An appraisal of the CORINE land cover database in airport catchment area analysis using a GIS approach. - Suau-Sanchez, Pere; Burghouwt, Guillaume; Pallares-Barbera, Montserrat (Elsevier, 2014)
This paper presents a free available dataset, the CORINE land cover that helps dealing with the biases caused by pre-defined and heterogeneous census district boundaries in airport catchment area analysis in Europe. Using this dataset and conventional GIS software it is possible to measure the size of the population within catchment areas at the same spatial level for all EU airports, allowing for consistent comparisons among airports. To illustrate the potential of the CORINE/GIS approach, the size of the population in the catchment areas of all European airports was determined. The empirical exercise has an aggregate perspective, but this database presents many other possibilities of analysis to perform in a case-by-case basis.